An enigmatic new genus of Hormiinae (Hymenoptera: Braconidae) from South India - Ranjith, A.p.; Belokobylskij, Sergey A.; Quicke, Donald L.j.; Kittel, Rebecca N.; Butcher, Buntika A.; Nasser, M. (Zootaxa, 2017)
A new Hormiinae genus Indohormius gen. nov. with type species I. keralensis sp. nov. is described and illustrated. Comparison of this genus with some Hormiinae and Rhyssalinae genera are provided. The composition of the subfamily Hormiinae and the position of the new genus on a molecular phylogenetic tree are discussed.